Respuesta :
Answer:
A.
Step-by-step explanation:
multiply the to equation by 6, multiply the bottom equation by -5 (you will get +30y and -30y to eliminate each other)then add equations (you will have +48x and +45x which will be = -42 + 20)
Answer: A multiply the top equation by 6, multiply the bottom equation by -5, then add the equations
Step-by-step explanation:
8x + 5y = 7
-7x + 6y = -4
multiply the top equation by 6, the equation becomes;
48x + 30y = 42 ----------(3)
multiply the bottom equation by -5, the equation becomes;
30x - 30y = 20-------(4)
adding equation (3) and (4) together;
+30y - 30y = 0
Therefore the y variable will be eliminated from the equation